Penyuluhan Peran Lembaga Keuangan Syariah dalam Pengembangan UMKM di Desa Ngaran, Polanharjo, Klaten - Yazid, Afthon; Huda, Nurul; Anwar, Qosim Khoiri (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
The development of Micro, Small and Medium Enterprises (MSMEs) has an important role in the village economy. One of the main factors in the development of MSMEs is access to adequate financing. Sharia Financial Institutions (LKS) have unique characteristics that can support the development of MSMEs with Islamic economic principles. This community service activity was carried out in Ngaran Polanharjo Village, Klaten, with the topic